PEMBELAJARAN MENULIS ESAI MELALUI TEKNIK MIND MAPPING RETENTION - Salamah Salamah; Hesti Hesti; Suhardi Suhardi (Universitas Negeri Makassar, 2023)
Writing Through Mind Mapping Retention Technique Innovation. The purpose of this research is to provide a reference for teaching writing literacy, especially writing essays in limited face-to-face learning. This research is experimental, with a research design including a pretest, treatment, and posttest. The sample for this study consisted of students of the Indonesian Language Education Study Program FKIP Muhammadiyah University of Lampung, consisting of as many as 28 students in one class. Research data were analyzed using descriptive and inferential statistics. The results of this study indicate that the posttest results have increased, so that the Mind Mapping Retention technique can be used in learning to write essays.